The Impact of Students’ Social Identity on Psycho-Social Adaptation during the Period of a Difficult Educational Transition - Zhylin, Mykhailo; Sikorskyi, Petro; Balla, Evelina; Barchan, Valentyna; Kuzma, Oksana (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Students' adaptation to the educational institution's social environment during difficult educational transitions is an important indicator of their success. Students can achieve full adaptation by identifying themselves with the social environment of the higher educational institution that is provided the developed social identity. So, the study aimed to empirically identify the psycho-social adaptation of students with different types of social identity during the transition to study in a higher educational institution. Methods: The research used standardized psychodiagnostic methods-questionnaires: "Methodology for studying social identity Schneider, L.B., & Khrustaleva, V. V.", " Methods of diagnostics socio-psychological adaptation of Karl Rogers and Rozalin Diamond (adaptation of A. Osnizkij)", " Method of Research of Students Adaptability in the Higher Educational Establishment T.D. Dubovitskaya, A.V. Krylova". Results: The obtained results revealed that students with a high level of positive identity have the highest indicators of socio-psychological adaptation and adaptability to higher educational institutions (p≤0.001). Students with identity diffusion have low socio-psychological adaptation and adaptability to learning (p≤0.001). The correlation analysis revealed statistically significant (p≤0.001) correlations between the type of social identity and adaptability to higher educational institutions. Correlations were also found at a high level of significance (p≤0.001) between the type of social identity and socio-psychological adaptation of students. It is empirically proven that the type of social identity affects the psychosocial adaptation of students during a difficult educational transition. Students with a high level of identity have a high psychosocial adaptation and adaptability to higher educational institutions. Further Implementation: The obtained results will contribute to developing a system for improving the psycho-social adaptation of students during the difficult educational transition through the development of social identity.